2020
DOI: 10.2147/dmso.s250699
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anti-Lipolysis Induced by Insulin in Diverse Pathophysiologic Conditions of Adipose Tissue</p>

Abstract: As an important energy reservoir, adipose tissue maintains lipid balance and regulates energy metabolism. When the body requires energy, adipocytes provide fatty acids to peripheral tissues through lipolysis. Insulin plays an important role in regulating normal fatty acid levels by inhibiting lipolysis. When the morphology of adipose tissue is abnormal, its microenvironment changes and the lipid metabolic balance is disrupted, which seriously impairs insulin sensitivity. As the most sensitive organ to respond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 111 publications
2
31
0
Order By: Relevance
“…Lipolysis is a process of TG breakdown into FFAs by lipase enzymes to meet energy requirements. The activation of β-adrenergic leads to cyclic adenosine phosphate (cAMP) production [ 15 ]. These cAMPs bind to protein kinase A (PKA) and stimulate the phosphorylation of lipase enzymes [ 16 ].…”
Section: Nafld Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Lipolysis is a process of TG breakdown into FFAs by lipase enzymes to meet energy requirements. The activation of β-adrenergic leads to cyclic adenosine phosphate (cAMP) production [ 15 ]. These cAMPs bind to protein kinase A (PKA) and stimulate the phosphorylation of lipase enzymes [ 16 ].…”
Section: Nafld Pathogenesismentioning
confidence: 99%
“…This PNPLA2 lipase hydrolyzes the ester bond of TG into diacylglycerol (DAG), and hormone-sensitive lipase mediates the hydrolysis of DAG to monoacylglycerol (MAG). Following this, the monoglyceride lipase catalyzes the hydrolysis of MAG to glycerol and FFAs [ 15 ]. Usually, circulating FFAs are higher during fasting and decrease upon feeding due to insulin signaling, suppressing lipolysis.…”
Section: Nafld Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning abdominal fat, AECT reduce the quantity in a dose-dependent manner with the highest reduction observed at 1250 mg/kg of AECT compared to the group of rats treated with metformin. In normal physiological state, insulin activates the lipolytic actions of the hormones on the deposit peripheral fat, hydrolyzing triglycerides and preventing storage of free fatty acids 39, 40 . In this experimental study, type 2 diabetic rats-showed significantly elevated quantity of abdominal fat.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is therefore usually regarded as a hepatic manifestation of the metabolic syndrome and diabetes. In healthy individuals, insulin inhibits hormone-sensitive lipase in adipose tissue, inhibiting triglyceride hydrolysis and free fatty acid (FFA) release [ 18 ]. In those with NAFLD, increased visceral adipocyte mass and the disinhibited activity of hormone-sensitive lipase in insulin resistance increase triglyceride hydrolysis, which increase plasma levels of FFAs, especially in the portal venous blood.…”
Section: Pathophysiology and Disease Progressionmentioning
confidence: 99%